Influence of intermittent steam injection into saline water: a study of wave motions in saline water for optimizing similar hydrodynamics in direct contact condensation based milk sterilization process - Khan, A. (Taylor and Francis Ltd., 2021)
The injection of steam into the water or saline involve intermittent wave structures that can affect the mass and heat transfer within fluid domain. It may be analogous to the processes prevailed in milk sterilization process as the boiling point of the saline water â¼100.50C is nearly the same as the milk. Steam was injected into the rectangular duct at varying gauge pressure of 0.5, 1.0 and 1.5 bars and the proximity sensors were used to determine the disturbances over the surface of the saline water, read as the amplitudes of the waves. The wavy profiles thus found as a result of intermittent injection of steam into the saline water included the longitudinal waves, reflected waves cross-channel transverse and the edge waves. The normalized wave provided the spatial locations for the interaction regions between the surface gravity waves with the longitudinally propagating waves. The longitudinal waves and reflected waves reveals the length scales at which the incident longitudinal waves have been dissipated. These waves have been dissipated 80-90 of their amplitudes due to viscous dissipation. Thus, the relation between their growth rate and injection time has been defined based on the observed results. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.